Prediksi Pengaruh Implementasi Kegiatan Pemberantasan Sarang Nyamuk (PSN) Terhadap Kejadian DBD - Meithyra Melviana Simatupang; Ely Yuliah (Jurnal Untuk Masyarakat Sehat (JUKMAS), 2021)
Eradication of Mosquito Nests (PSN) in community environment is the prior focus of dengue hemorrhagic fever (DHF) prevention and control, implemented through the practice of eliminating breeding sites and avoiding mosquito bites. The aimed of the study was to determine the most influence of PSN practice against the incidents of DHF. The case control study arranged at Puskesmas Kecamatan Ciracas Jakarta Timur work area, then interviewed sample from case and control group, as many as 47 people from each group. Samples of case group were DHF patients who registered at medical record of Puskesmas Ciracas in January-April 2020. While samples from control group were the closest neighborhood of every case sample with similiar characteristic by age group, sex, and house environment. Nevertheless, research respondent which will be interviewed to collect data had to more than 15 years old to prevent information bias. Positive correlation against DHF incidents proved by bivariat analysis of draining water container, using container lid, unused stuff management, using repellent, and keeping larvivorous fish. Among of those factors, logistic regression test showed regularly drained water container once a week had the most effect to DHF incident. At th[1]          Kemenkes RI. Pedoman Demam Berdarah Dengue Indonesia. In Jakarta; 2017.[2]          Direktorat Jenderal Pengendalian Penyakit dan Penyehatan Lingkungan KKR. Buku Saku Pengendalian Demam Berdarah Dengue Untuk Pengelola Program DBD Puskesmas. 2013.[3]          WHO. Dengue: Guidelines for Diagnosis, Treatment, Prevention and Control. Geneva, editor. World Health Organization; 2010.[4]          Dinas Kesehatan DKI Jakarta. Surveilans DKI Jakarta. 2020.[5]          Novrita B, Mutahar R, Purnamasari I. Analisis Faktor Risiko Kejadian Demam Berdarah Dengue Di Wilayah Kerja Puskesmas Celikah Kabupaten Ogan Komering Ilir. J Ilmu Kesehat Masy [Internet]. 2017;8(1):19–27. Available from: https://www.google.com/url?sa=t&rct=j&q=&esrc=s&source=web&cd=&cad=rja&uact=8&ved=2ahUKEwjqiI6cp67sAhVCX30KHeaRBzcQFjACegQIARAC&url=http%3A%2F%2Fjikm.unsri.ac.id%2Findex.php%2Fjikm%2Farticle%2Fdownload%2F399%2Fpdf&usg=AOvVaw29QAdaCsOoTMQSSOqPIVCw[6]          Ayun LL, Pawenang ET. Hubungan antara Faktor Lingkungan Fisik dan Perilaku dengan Kejadian Demam Berdarah Dengue (DBD) Di Wilayah Kerja Puskesmas Sekaran, Kecamatan Gunungpati, Kota Semarang. Public Heal Perspect J [Internet]. 2017;2(1):97–104. Available from: https://journal.unnes.ac.id/nju/index.php/phpj/article/viewFile/11002/6680[7]          Sari TW, Putri R. Pemberantasan Sarang Nyamuk 3M Plus terhadap Kejadian Demam Berdarah Dengue di Puskesmas Payung Sekaki Kota Pekanbaru: Studi Kasus Kontrol. J Epidemiol Kesehat Indones [Internet]. 2019;3(2):55–60. Available from: http://journal.fkm.ui.ac.id/epid/article/view/1781[8]          Vannavong N, Seidu R, Stenström T-A, Dada N, Overgaard HJ. Effects of Socio-demographic Characteristics and Household Water Management on Aedes aegypti Production in Suburban and Rural Villages in Laos and Thailand. Parasit Vectors. 2017;10.[9]          Saleh M, Aeni S, Gafur A, Basri S. Hubungan Pemberantasan Sarang Nyamuk (PSN) dengan Keberadaan Jentik Nyamuk Aedes aegypti di Wilayah Kerja Puskesmas Pancana Kab. Barru. Higiene [Internet]. 2018;4(2):93–8. Available from: https://core.ac.uk/download/pdf/234747865.pdf[10]        Sitepu FY, Nasution H, Supriyadi T, Depari E. Epidemiological and Entomological Investigation of Dengue Fever Outbreak in South Nias District North Sumatera Province Indonesia 2016. Outbreak, Surveillance, Investig Response. 2018;11(3):8–12.[11]        Rosmal F, Rosidah I. Hubungan Faktor Resiko Kesehatan Lingkungan Dalam Pengelolaan Sampah Padat Dengan Kejadian Demam Berdarah Dengue di Kelurahan Hegarsari Kecamatan Pataruman Kota Banjar. J Kesehat Komunitas Indones [Internet]. 2019;15(1):23–34. Available from: http://jurnal.unsil.ac.id/index.php/jkki/article/viewFile/986/785[12]        He P, Chen L, Shao L, Zhang H, Lü F. Municipal Solid Waste (MSW) landfill: A source of microplastics? Evidence of Microplastics in Landfill Leachate. Water Res [Internet]. 2019;159:38–45. Available from: https://www.sciencedirect.com/science/article/abs/pii/S004313541930377X[13]        Harsono S, Nisaa A. Metode Biokontrol Ikan Cupang (Betta splendens) Sebagai Pengendali Vektor Penyakit DBD di Kartasura Kabupaten Sukoharjo. J Manaj Inf dan Adm Kesehat. 2019;2(2):38–43.[14]        Sarwar M. Control of Dengue Carrier Aedes Mosquitoes (Diptera: Culicidae) Larvae by Larvivorous Fishes and Putting It into Practice Within Water Bodies. Int J Prev Med Res [Internet]. 2015;1(4):232–7. Available from: http://www.aiscience.org/journal/ijpmr[15]        Hartati AT, Rusmartini T, Ismawati. Uji Kemampuan Ikan Manfish (Pterophyllum altum), Ikan Cupang (Betta splendens), dan Ikan Cere (Gambusia affinis) Sebagai Predator Larva Aedes aegypti dalam Upaya Penanggulangan DBD. Pros Pendidik Dr Unisba. 2016;2(2).[16]        Ishak H, Aisyah AS, Mallongi A, Astuti RDP. Risk factors and Fogging Effectiveness of Dengue Hemorrhagic Fever Incidence in the Pontap Public Health Center area in Palopo City, Indonesia_. Enferm Clin [Internet]. 2020;30:294–7. Available from: https://www.researchgate.net/publication/342113828_Risk_factors_and_fogging_effectiveness_of_dengue_hemorrhagic_fever_incidence_in_the_Pontap_Public_Health_Center_area_in_Palopo_City_Indonesia[17]        Bowman LR, Donegan S, McCall PJ. Is Dengue Vector Control Deficient in Effectiveness or Evidence?: Systematic Review and Meta-analysis. PLoS Negl Trop Dis [Internet]. 2016;10(3). Available from: https://journals.plos.org/plosntds/article?id=10.1371/journal.pntd.0004551[18]        Farich A, Perdana AA. Efektifitas Penanaman Tanaman Serai Wangi (Cymbopogon nardus) Terhadap Indikator Maya Index DBD di Kabupaten Pringsewu, Lampung. J Dunia Kesmas [Internet]. 2019;8(4). Available from: http://ejurnalmalahayati.ac.id/index.php/duniakesmas/article/view/190-198/pdf[19]        Erlia D, Darusman F, Darma GCE. Pembuatan Briket Penghalau Nyamuk (Repellent) dari Daun Serai Wangi (Cymbopogon winterianus Jowitt) dan Evaluasinya. Farmasi [Internet]. 2016;2(2). Available from: http://karyailmiah.unisba.ac.id/index.php/farmasi/article/view/4706[20]        Misni N, Nor ZM, Ahmad R. New Candidates For Plant Based Repellents Against Aedes Aegypti. J Am Mosq Control Assoc [Internet]. 2016;32(2):117–123. Available from: https://www.researchgate.net/publication/303887327_New_Candidates_for_Plant-Based_Repellents_Against_Aedes_aegypti[21]        Priesley F, Reza M, Rusjdi SR. Hubungan Perilaku Pemberantasan Sarang Nyamuk dengan Menutup, Menguras dan Mendaur Ulang Plus (PSN M Plus) terhadap Kejadian Demam Berdarah Dengue (DBD) di Kelurahan Andalas. J Kesehat Andalas [Internet]. 2018;7(1):124–30. Available from: http://jurnal.fk.unand.ac.id/index.php/jka/article/view/790/64622.         Liu J, Tian X, Deng Y, Du Z, Liang T, Hao Y, et al. Risk Factors Associated with Dengue Virus Infection in Guangdong Province: A Community-Based Case-Control Study. Int Environ Res Public Heal [Internet]. 2019;16. Available from: https://www.ncbi.nlm.nih.gov/pmc/articles/PMC6406885/[23]        Husna I, Putri DF, Triwahyuni T, Kencana GB. Analisis Faktor yang Mempengaruhi Kejadian Demam Berdarah Dengue di Wilayah Kerja Puskesmas Way Kandis Bandar Lampung Tahun 2020. J Anal Kesehat [Internet]. 2020;9(1):9–16. Available from: https://www.google.com/url?sa=t&rct=j&q=&esrc=s&source=web&cd=&cad=rja&uact=8&ved=2ahUKEwiAt8WG17DsAhUBA3IKHZ1qCXYQFjAKegQIChAC&url=https%3A%2F%2Fejurnal.poltekkes-tjk.ac.id%2Findex.php%2FJANALISKES%2Farticle%2Fdownload%2F2111%2F1109&usg=AOvVaw3JEApbZPpsukTr9HHVeBEN[24]        Ramadhani F, Yudhastuti R, Widati S. Consciousness Stage Implementation of Mosquito Nest Eradication (MNE) of Dengue Hemorrhagic Fever (DHF). Heal Notions [Internet]. 2017;1(3). Available from: http://heanoti.com/index.php/hn/article/view/hn1305[25]        Saied KG, Al-Taiar A, Altaire A, Alqadsi A, Alariqi EF, Hassaan M. Knowledge, Attitude and Preventive Practices Regarding Dengue Fever in Rural Areas of Yemen. Int Health [Internet]. 2015;7:420–5. Available from: https://academic.oup.com/inthealth/article/7/6/420/2458785[26]        Wong LP, Shakir SMM, Atefi N, AbuBakar S. Factors Affecting Dengue Prevention Practices: Nationwide Survey of the Malaysian Public. PLoS One. 2015;[27]        Elsinga J, Schmidt M, Lizarazo EF, Vincenti-Gonzalez MF, Velasco-Salas ZI, Arias L, et al. Knowledge, Attitudes, and Preventive Practices Regarding Dengue in Maracay, Venezuela. Am J Trop Med Hyg. 2018;99(1):195–203.[28]        Rakhmani AN, Limpanont Y, Kaewkungwal J, Okanurak K. Factors Associated with Dengue Prevention Behaviour in Lowokwaru, Malang, Indonesia: a Cross-sectional Study. BMC Public Health [Internet]. 2018;18. Available from: https://www.ncbi.nlm.nih.gov/pmc/articles/PMC5948848/pdf/12889_2018_Article_5553.pdf e same time, used of container lid had no significance value, so that was being expelled from model of multivariate analysis. Based on this result, it can be predicted that respondent who not drained water container, not used repellent, not kept larva-eating fish, and not manage unused stuff will suffer DHF.Keywords : drained container, repellent, larvivorous fish, manage unused stuff, DHF